2008
DOI: 10.5194/bg-5-1741-2008
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria in Himalayan glacial ice and its relationship to dust

Abstract: Abstract. Concentrations and community diversity of bacteria from 50 segments of a 108.83 m ice core drilled from the East Rongbuk (ER) Glacier (28.03 • N, 86.96 • E, 6518 m above sea level) on the northeast slope of Mt. Qomolangma (Everest), covering the period 950-1963 AD, were investigated by epifluorescence microscope, DGGE and ShannonWeaver index analysis. Bacteria in the ER core were identified as β, γ -proteobacteria and Firmicutes group, with γ -proteobacteria being the dominance. Different bacterial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Previous studies have shown the prevalence of specific bacteria in certain local glaciers (Zhang et al, 2008; Xiang et al, 2009; An et al, 2010; Franzetti et al, 2013; Miteva et al, 2015). However, our findings demonstrate that the members of bacterial genus-related groups are highly similar in the related ice cores at a historical scale, whereas the composition of the prevalent genus-related groups is largely different across the geographically different glaciers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the prevalence of specific bacteria in certain local glaciers (Zhang et al, 2008; Xiang et al, 2009; An et al, 2010; Franzetti et al, 2013; Miteva et al, 2015). However, our findings demonstrate that the members of bacterial genus-related groups are highly similar in the related ice cores at a historical scale, whereas the composition of the prevalent genus-related groups is largely different across the geographically different glaciers.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few taxonomic groups are able to colonize and dominate in the snow, although numerous microorganisms are trapped in the surface snow (Zhang et al, 2008, 2009; Xiang et al, 2009, 2010; An et al, 2010). Previous limited data of glacier surface snow have shown that the bacteria Comamonadaceae and Flavisolibacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…The dating of these cores can go back to the past 2000 yr, with a time resolution from annual scales for the upper part of ice core to decadal for the lower part (Xu and Yao, 2001;Hou et al, 2004). Invaluable climatic and environmental information in the central high Himalayas has been revealed by these ice cores, such as regional warming (Thompson et al, 2000b;Hou et al, 2007), atmospheric pollution induced by anthropogenic activities since the industrial revolution (Duan et al, 2007;Kaspari et al, 2009b;Hong et al, 2009), precipitation variations over the central Himalayas (Duan et al, 2004; centuries (Kaspari et al, 2009a;Xu et al, 2010), black carbon concentrations (Ming et al, 2008;Kaspari et al, 2011), and bacterial information (Zhang et al, 2007(Zhang et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Layered distribution of bacterial isolates within ice cores was thought to originate from diverse bacterial sources which could have been different in the past (55,57). It has been shown that dust concentration is more important in determining bacterial diversity than bacterial abundance in the Himalayan glaciers (57), a fact which could highlight the importance of aeolian transport conditions: therefore, the study of microorganisms trapped in ice might be useful for the reconstruction of past climatic and environmental changes (57).…”
mentioning
confidence: 99%